2/3n=4n-10/3n-12

Simple and best practice solution for 2/3n=4n-10/3n-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3n=4n-10/3n-12 equation:



2/3n=4n-10/3n-12
We move all terms to the left:
2/3n-(4n-10/3n-12)=0
Domain of the equation: 3n!=0
n!=0/3
n!=0
n∈R
Domain of the equation: 3n-12)!=0
n∈R
We get rid of parentheses
2/3n-4n+10/3n+12=0
We multiply all the terms by the denominator
-4n*3n+12*3n+2+10=0
We add all the numbers together, and all the variables
-4n*3n+12*3n+12=0
Wy multiply elements
-12n^2+36n+12=0
a = -12; b = 36; c = +12;
Δ = b2-4ac
Δ = 362-4·(-12)·12
Δ = 1872
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1872}=\sqrt{144*13}=\sqrt{144}*\sqrt{13}=12\sqrt{13}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(36)-12\sqrt{13}}{2*-12}=\frac{-36-12\sqrt{13}}{-24} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(36)+12\sqrt{13}}{2*-12}=\frac{-36+12\sqrt{13}}{-24} $

See similar equations:

| 6i+7=13+5i | | 4(2x+8)=−16 | | 248=-8(-6p+5) | | 33+31+p=131 | | 1/4(2x+8)=−16 | | 2(3b+5)=4(b-5) | | -7x+33=-5(x-3) | | 4/3x-6=2 | | .30p=1/2p-8 | | -x/2=2 | | -11x-20+5x=1-3x | | 4x-13=-15+4x | | 2(2h+3)-2=8 | | -17x+3=12x+17 | | (24+y)+y=180 | | 1/2(d-7)-4/3(2d-4)=5/6 | | 33-7x=20+6x | | 180=2x+22+5x+39 | | 14+18=m-42 | | Y=0.25x^-3 | | 1.5x+1.4x=18 | | 0=-8m-24 | | 27.38=y | | -2(g+2)+6g=-2 | | 24+y+y=180 | | -2x-40=3x | | 4x+11=8x+19 | | -14=10q+36 | | 26=10+x+13 | | 2(f-4)=16 | | 9x+20=8x-11 | | 7-8/3b=-5+b |

Equations solver categories